2020
DOI: 10.29253/achnr.2020.23958
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nutritional Status of Pregnant Women

Abstract: Malnutrition in pregnant women has an impact on both mother and child.  In children causing LBW, premature, developmental disorders, stunting. Mother, it causes chronic energy deficiency and anemia. Therefore important to conduct literature studies regarding factors that affect the nutritional status of pregnant women. This literature study is purposeful to identify the influencing factors nutritional status of pregnant women and knowing whether there are other factors besides those that have been widely studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Individuals become able to better understand through the educational process [25]. The lack of information about pregnant women's nutritional status will impact the food they consume [26]. Nevertheless, a mother with a lower education does not mean she does not have information about health during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals become able to better understand through the educational process [25]. The lack of information about pregnant women's nutritional status will impact the food they consume [26]. Nevertheless, a mother with a lower education does not mean she does not have information about health during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Expectant mothers with more than three pregnancies are prone to CED. High parity also necessitates that women focus on their children rather than on their own diet and health state [26]. Grand multiparity has been shown to cause an increased risk of obstetric and medical issues, including anemia, birth asphyxia, preterm birth, low birth weight, macrosomia, stillbirth, and a high perinatal mortality rate, according to the evidence [31].…”
Section: Resultsmentioning
confidence: 99%
“…identi ed in literature as the optimal age for healthy and safe reproduction 15 16 4 . Moreover, prior studies have suggested that ages that are too low, i.e., less than 20 years, may be biologically unprepared and mentally immature for pregnancy 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the age category of 26-35 years was found to be comparable to the age category of 20-35 years, which has been previously identi ed in literature as the optimal age for healthy and safe reproduction 15 16 4 . Moreover, prior studies have suggested that ages that are too low, i.e., less than 20 years, may be biologically unprepared and mentally immature for pregnancy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in this study considering significant relations between overall empowerment and nutrition outcomes of pregnant women. Moreover, it has been underlined that the nutritional status of pregnant women depends on multiple factors such as dietary habit, access to health services, infectious diseases, and knowledge ( 71 ) besides the independent and control variables considered in this study. Excluding these factors may have affected our study results.…”
Section: Discussionmentioning
confidence: 99%